Biodiesel production from soybean oil using ionic liquid as a catalyst in a microreactor - F. Mohammadi; M. Rahimi; A. Parvareh; M. Feyzi (Iranian Journal of Chemical Engineering)
In the present study, Choline hydroxide (ChOH) as an ionic liquid catalyst was used for transesterification of soybean oil into biodiesel in a microchannel reactor. The effects of three variables i.e. reaction temperature, catalyst dosage and total flow rate on fatty acid methyl ester (FAME) content (wt. %) were optimized using Box–Behnken experimental design. In order to predict the FAME content a quadratic polynomial model was obtained. The optimal conditions from the model were reaction temperature of 53.53 °C, catalyst dosage of 2.6 wt. % and total flow rate of 11.82 mL/min. At these conditions, the predicted FAME content was 96.45 wt.% and the experimental FAME content was obtained 97.6 wt. %. The proximity of the experimental results and predicted values showed that the regression model issignificant. Using the ionic liquid catalyst in the studied microreactor for transesterification leads to diminish the reaction time to the order of seconds compared to conventional batch systems. In addition, the reusability of ChOH catalyst was investigated. The results revealed that the catalyst had perfect utility after several runs without much loss in the activity.